Attention Improvement through Play Puzzle Therapy to Promote Self-Regulation in Children with Attention Deficit Hyperactivity Disorder (ADHD) - Winarsunu, Tulus; Hanapi, Trie Nurfadillah; Fasikhah, Siti Suminati (Journal of Educational, Health and Community Psychology, 2022)
Attention Deficit Hyperactivity Disorder (ADHD) is a pervasive developmental disorder that results in individuals having difficulties organizing behavior to be more focused because of the need to always seek stimulation from the environment, which causes problems in self-regulation. The thing that causes children to have difficulties managing stimuli from the environment is their difficult condition to focus or inattention. This study aimed to determine the effect of attention and self-regulation in children with ADHD and to see the effect of increased attention on improving self-regulation of children with ADHD through play therapy with puzzles. The design of this study was a non-equivalent control group design. The technique of taking the subject used purposive sampling. The scale used to measure the pretest and post-test was the Indonesian Hyperactive Child Rating Scale (SPPHAI) to measure the attention, and the Self Control Rating Scale (SCRS) to measure self-regulation. Our results seems indicated a positive effect of attention improvement on self-regulation development in children with ADHD through play puzzle therapy. The experimental group receiving puzzle play therapy had better self-regulation compared to the control group receiving no treatment. The experimental group subjects also showed a lower increase of self-regulation based on the research results.Â  This fact clarified that there are other potential contributing factors in the improved self-regulation among control group subjects. This study concluded that there was an effect of increasing attention to self-regulation through a therapy of playing puzzles in children with ADHD conditions.